2015
DOI: 10.1055/s-0034-1391563
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter pragmatic study of an evidence-based intervention to improve adenoma detection: the Quality Improvement in Colonoscopy (QIC) study

Abstract: In routine clinical practice, introduction of a simple, inexpensive, evidence-based "bundle" of measures is feasible and is associated with higher global ADR, driven by improvements amongst the poorest performing colonoscopists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Therefore, guidelines recommend at least 6 min of withdrawal time as a quality marker [4,46,47]. Longer withdrawal times frequently result in a higher ADR just as data from the QIC study demonstrate [48]. There are several studies that underline this important finding [49,50].…”
Section: Factors Influencing the Adrmentioning
confidence: 99%
“…Therefore, guidelines recommend at least 6 min of withdrawal time as a quality marker [4,46,47]. Longer withdrawal times frequently result in a higher ADR just as data from the QIC study demonstrate [48]. There are several studies that underline this important finding [49,50].…”
Section: Factors Influencing the Adrmentioning
confidence: 99%
“…A recent large multicenter study from the UK (Quality Improvement in Colonoscopy study) found that implementation of a bundle of measures (e.g. withdrawal time ≥6 min, use of butylscopolamine, position change during colonoscopy to optimize visualization, and rectal retroflexion) improves adenoma detection rates . To improve uniformity in surveillance practice, the post‐polypectomy surveillance guidelines of the ESGE recommend risk stratification in two groups: (i) low‐risk group, which consists of patients with one or two non‐advanced adenomas versus (ii) high‐risk group, which consists of patients with ≥three adenomas or ≥one advanced adenoma (≥10 mm, villous histology or high‐grade dysplasia).…”
Section: Detection and Resection Of Colorectal Neoplasmsmentioning
confidence: 99%
“…Many of the strategies for improving the quality in colonoscopy have an evidence base to support them 4. Interventional ‘bundles’ have already been used to try to increase quality markers such as ADR 25. Introduction with feedback of a ‘bundle’ (withdrawal time >6 mins, use of buscopan, rectal retroflexion and dynamic position changes) improved detection, especially among poor performers, with benefits maintained for 3 years postintervention 26.…”
Section: Introductionmentioning
confidence: 99%